TERTIUS GAUDENS PADA JARINGAN KOMUNIKASI KRIMINAL DI INSTITUSI PEMERINTAH: Studi Kasus Pembunuhan Josua Hutabarat dalam Detik.com - Mohammad Ichlas El Qudsi; Asyam Ahmad Fatin (Jurnal Komunikasi & Media Digital, 2024)
This research is motivated by the existence of communication networks found in various institutional layers related to various things, for example crime. One of them occurs in government law enforcement institutions such as the police. The aim is to see how networks occur in institutions and which third parties (tertius gaudens) benefit most from this. This research uses quantitative network analysis with data sources from online media as a source of information. Of the 637 news stories, the narratives of 46 actors were found to be involved with 16 actors as tertius gaudens. Actor 16 becomes tertius gaudens because of his important position in this case.